2015
DOI: 10.1002/lno.10220
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilatory nitrate reduction to ammonium coupled to Fe(II) oxidation in sediments of a periodically hypoxic estuary

Abstract: Estuarine sediments are critical for the remediation of large amounts of anthropogenic nitrogen (N) loading via production of N 2 from nitrate by denitrification. However, nitrate is also recycled within sediments by dissimilatory nitrate reduction to ammonium (DNRA). Understanding the factors that influence the balance between denitrification and DNRA is thus crucial to constraining coastal N budgets. A potentially important factor is the availability of different electron donors (organic carbon, reduced iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 74 publications
9
105
1
Order By: Relevance
“…Most known Fe(II)-oxidizing NO 3 − -reducing microbes live mixotrophically and therefore require an organic carbon source for the oxidation of Fe(II) over a long period (Hansen et al 1996;Straub et al 2004). Recently, researchers confirmed that NO 3 − reduction coupled to Fe(II) oxidation can be catalyzed by microorganisms (Robertson et al 2016). They determined stoichiometries of Fe(II) oxidation and nitrate reduction in microcosm incubations and the incorporation of 14 C from labeled bicarbonate and proved the existence of autotrophic Fe(II)-oxidizing NO 3 − -reducing bacteria in marine sediments.…”
Section: Anaerobic Hcomentioning
confidence: 89%
“…Most known Fe(II)-oxidizing NO 3 − -reducing microbes live mixotrophically and therefore require an organic carbon source for the oxidation of Fe(II) over a long period (Hansen et al 1996;Straub et al 2004). Recently, researchers confirmed that NO 3 − reduction coupled to Fe(II) oxidation can be catalyzed by microorganisms (Robertson et al 2016). They determined stoichiometries of Fe(II) oxidation and nitrate reduction in microcosm incubations and the incorporation of 14 C from labeled bicarbonate and proved the existence of autotrophic Fe(II)-oxidizing NO 3 − -reducing bacteria in marine sediments.…”
Section: Anaerobic Hcomentioning
confidence: 89%
“…Fermentative DNRA consists of the reduction of NO 3 − to NO 2 − to produce energy, and then to NH 4 + to allow reoxidation of NADH 5 (Tiedje, 1988). Chemoautotrophic DNRA consists of the reduction of NO 3 − using sulfide (S -2 ), elemental S, or Fe +2 as electron donors (Robertson et al, 2016;Slobodkina et al, 2017 In fermentative DNRA, the initial reduction of NO 3 − to NO 2 − occurs in the same way as in denitrification and is catalyzed by either the periplasmic nitrate reductase complex (NapAB) or the membrane-bound nitrate reductase complex (NarGHI) (Moreno-Vivián et al, 1999). The reduction of NO 2 − to NH 4 + is catalyzed by the cytochrome C nitrite reductase (NrfA).…”
Section: Dissimilatory Nitrate Reduction To Ammonia (Dnra)mentioning
confidence: 99%
“…The abundance of nrfA genes is correlated with S -2 and Fe 2+ , which can enhance DNRA by providing extra free energy (Robertson et al, 2016;Yin et al, 2017). Elevated temperatures increase DNRA rates; therefore, DNRA may be an important pathway for NO 3 − conversion during summer (Yin et al, 2017).…”
Section: 41mentioning
confidence: 99%
“…Reactive Fe minerals, such as oxides, sulfides, phosphates and carbonates, are involved in diagenetic reactions in sediments and consequently influence the cycling of carbon and nutrients (e.g., Berner, 1970;Slomp et al, 1996a,b;Lovley et al, 2004;Jilbert and Slomp, 2013;Kraal et al, 2015;Robertson et al, 2016). Iron has also recently been shown to stabilize organic carbon in sediments, promoting carbon 5 burial (Lalonde et al, 2012;Shields et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Fe has recently been suggested to play an important role in carbon burial (Lalonde et al, 2012;Shields et al, 2016) and nitrogen cycling (Robertson et al, 2016) in marine sediments. 15…”
Section: Introductionmentioning
confidence: 99%